The Implementation of Flexibility Strategy on Agricultural Commodity Financing With Warehouse Receipt System - Karmex Siadari; M.Syamsul Maarif; Bustanul Arifin; Zulkifli Rangkuti (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The implementation of warehouse receipt financing system for agriculture commodities has not been successfully developed in Indonesia, some constraints are hindering the system to grow. Flexibility strategy is conceptually applicable to minimize gaps in the system to its environment. This research was conducted to determine an adaptive warehouse receipt financing system using strategic flexibility. The research was carried out by ways in-depth interviews and focus group discussions with respondents with knowledge of or experience in warehouse receipt financing systems for commodities such as coffee, pepper, rice and maize. Analysis was done using Soft System Methodology (SSM) and Interpretive Structural Model (ISM) analysis to define conceptual models of flexibility strategy applied in warehouse receipt financing systems. The research findings, flexibility strategy is applicable in the warehouse receipt financing system: applying resource flexibility on input side to select the most efficient material to develop the product, applying resource and coordination flexibility in internal process to optimize internal processing, applying internal resources and coordinating flexibility on output distribution to expand the market and applying coordination flexibility to respond external condition. However, applying a flexibility strategy to respond externally was found to be the most suitable to adapt agriculture commodities financing on warehouse receipt system to its environment. Keywords: agricultural commodities, financing constraints, flexibility strategy, warehouse receipt system